Search for the rare decays B+→μ+μ-K+, B0→μ+μ- K*(892)0, and Bs0→μ+μ- at CDF - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; et al. (2009)
We search for b→sμ+μ- transitions in B meson (B+, B0, or Bs0) decays with 924pb-1 of pp̄ collisions at s=1.96TeV collected with the CDF II detector at the Fermilab Tevatron. We find excesses with significances of 4.5, 2.9, and 2.4 standard deviations in the B+→μ+μ-K+, B0→μ+μ-K*(892)0, and Bs0→μ+μ- decay modes, respectively. Using B→J/ψh (h=K+, K*(892)0,) decays as normalization channels, we report branching fractions for the previously observed B+ and B0 decays, B(B+→μ+μ-K+)=(0.59±0.15±0. 04)×10-6, and B(B0→μ+μ-K*(892)0)=(0.81±0. 30±0.10)×10-6, where the first uncertainty is statistical, and the second is systematic. We set an upper limit on the relative branching fraction B(Bs0→μ+μ-)/B(Bs0→J/ψ)<2.6(2.3)×10-3 at the 95(90)% confidence level, which is the most stringent to date. © 2009 The American Physical Society.